Stimulasi Kognitif Melalui Aroma Kopi: Strategi Non-Farmakologis untuk Meningkatkan Konsentrasi Mahasiswa - Lestari, Laila Indra; Wimaswara, Aufa Angga (Flourishing Journal, 2025)
Concentration is a crucial cognitive aspect that influences undergraduate students’ academic success, and various sensory stimuli, such as aroma, may play a role in enhancing it. This study aimed to examine the effect of coffee aroma on students’ concentration. The proposed hypothesis was that coffee aroma has a significant effect on increasing concentration. The research employed an experimental design with two groups: an experimental group exposed to coffee aroma and a control group with no aroma exposure. The study participants consisted of 63 university students selected through purposive sampling. Concentration was measured using the Concentration Grid Test (CGT) based on the number of correct answers obtained. All participant data were analyzed after passing a manipulation check and statistical assumption tests. The results of the independent sample t-test showed a significant difference between the experimental group (M = 14.4, SD = 3.25) and the control group (M = 13, SD = 2.60), t(58) = 1.80, p = 0.03, d = 0.46. These findings indicate that exposure to coffee aroma can significantly improve students’ concentration. The implications of this study suggest that olfactory stimuli, such as coffee aroma, have potential as a non-pharmacological strategy to support cognitive performance in academic settings. AbstrakKonsentrasi merupakan salah satu aspek kognitif penting yang memengaruhi keberhasilan akademik mahasiswa, dan berbagai stimulus sensorik seperti aroma dapat berperan dalam meningkatkannya. Penelitian ini bertujuan untuk menguji pengaruh aroma kopi terhadap konsentrasi mahasiswa. Hipotesis yang diajukan adalah bahwa aroma kopi berpengaruh signifikan terhadap peningkatan konsentrasi mahasiswa. Desain penelitian menggunakan eksperimen dengan dua kelompok, yaitu kelompok eksperimen yang terpapar aroma kopi dan kelompok kontrol yang tidak terpapar. Pengukuran konsentrasi dilakukan menggunakan Concentration Grid Test (CGT) berdasarkan jumlah jawaban benar yang diperoleh. Seluruh data partisipan dianalisis setelah melalui manipulation check dan uji asumsi statistik. Hasil analisis Independent Sample t-Test menunjukkan adanya perbedaan signifikan antara kelompok eksperimen (M=14,4; SD=3,25) dan kelompok kontrol (M=13; SD=2,60), t (58)=1,80, p=0,03, d=0,46. Temuan ini mengindikasikan bahwa paparan aroma kopi dapat meningkatkan konsentrasi mahasiswa secara signifikan. Implikasi penelitian ini menunjukkan bahwa stimulus olfaktori seperti aroma kopi berpotensi digunakan sebagai strategi non-farmakologis untuk mendukung performa kognitif di lingkungan akademik.